2019
DOI: 10.1088/1742-6596/1364/1/012066
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and analysis of the solar photovoltaic levelized cost of electricity (LCoE) - case study in Kupang

Abstract: This paper presents a modeling and analysis of the levelized cost of electricity (LCoE) related to solar Photovoltaic (PV) power plants. As the PV matures, the economic feasibility of PV projects is increasingly being evaluated using the LCoE. Regulation of the Minister of Energy and Mineral Resources of the Republic of Indonesia Number 19 the Year 2016 concerning the purchase of electricity from PV Power Plants by PT PLN (Persero) for On-Grid PV in East Nusa Tenggara with a purchase of 0.23 US$ / kWh, but the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 11 publications
1
6
0
Order By: Relevance
“…It was noted that the battery storage costs constitute 67% of total capital costs, and further, they add to the operational costs. The analysis showed that the LCOE of the battery-integrated floating PV system is at the level of 261-349 USD/MWh, which is aligned with the case study conducted for off-grid solar PV in Indonesia with the LCOE range from 290 to 310 USD/MWh [25].…”
Section: Capital Costssupporting
confidence: 74%
“…It was noted that the battery storage costs constitute 67% of total capital costs, and further, they add to the operational costs. The analysis showed that the LCOE of the battery-integrated floating PV system is at the level of 261-349 USD/MWh, which is aligned with the case study conducted for off-grid solar PV in Indonesia with the LCOE range from 290 to 310 USD/MWh [25].…”
Section: Capital Costssupporting
confidence: 74%
“…Therefore, a simple calculation shows that a 3.3 MW turbine does not increase the capacity by five times to a 660 kW turbine, while the rotor diameter is only 2.54 times, and for a 2 MW wind turbine, it increases by 3.3 times compared to 660 kW. At the same time, the rotor diameter has increased only 2.3 times [30][31][32][33][34].…”
Section: Resultsmentioning
confidence: 99%
“…Fifth, when it comes to the levelised cost of electricity (LCOE), which is the unit cost of electricity (kWh or MWh) over the economic life or full life of a project [81,82], there is a lack of literature on the LCOE of BIPV systems. Several studies have investigated the LCOE of photovoltaics systems [83][84][85][86][87][88][89][90][91][92][93][94], but none of them investigated the BIPV systems. However, the economic analysis of BIPV systems and their LCOE is different from the PV systems.…”
Section: Problem Statement and The Scopementioning
confidence: 99%